Design of Expert System for Identification of Learning Modalities and Multiple Intelligences in Students with Fuzzy Logic Method - Nova Fatmasari; Eva Rianti; Hari Marfalino (Universitas Putra Indonesia YPTK Padang, 2024)
Multiple intelligences and learning modalities possessed by each student need to be considered by teachers. Because to maximize the learning process, both of these things are needed. However, this is often ignored by teachers. The learning process that is carried out only focuses on single intelligence and learning methods that focus on paying attention to the teacher explaining the material. This method certainly causes the learning process to be less than optimal. therefore , an expert system is needed that can help teachers and students know this. The expert system that will be processed takes knowledge from the Guidance and Counseling teacher of SMAN 15 Padang using the Fuzzy Logic Tsukamoto method. This expert system is processed using the Visual Basic.Net programming language, this expert system can identify 4 types of multiple intelligences, namely linguistics, mathematical logic, music and intrapersonal and also the learning modalities possessed by each student with predetermined rules. The results of the expert system can help teachers and students in improving the learning process. With this system, it can help schools, especially Guidance and Counseling teachers, in identifying the types of learning and multiple intelligences possessed by each student. So that it can develop and provide solutions for developing student abilities.